Hazards identification for safety and risk evaluation of hydroelectric dam power generation plant / Ali Mohammad Saedi - Saedi, Ali Mohammad (2013)
There are many formal techniques for the systematic analysis of occupational safety and health in general as well as specific areas. Currently there is increased interest in the evaluation of environmental safety and health. In the light of this a project was initiated for the evaluation of environmental safety and health at the Sultan Yusuf Hydro Electric Power generation Plant (JOR Power Station) at Cameron Highlands in Pahang. It was with a view to creating a conceptual framework for hazard identification and risk assessment at the power generating station of the plant and to recommend control measures with respect to environmental safety and health for the people, particularly the employees and workers, the process and the environment. In this study hazard identification was used to identify the primary and secondary or specific hazards which may be inherent in the system and determined as serious threat for plant operation and maintenance. The following methods were used to identify hazards at the JOR hydroelectric Power Station: checklists, work place inspection which included observation and interview, task safety analysis or job hazard analysis as well as accident and incident investigation. For risk assessment, the Likert scale was complemented by the Severity matrix analysis in order to determine the probability and extent of the situation at the Power generation plant. Together with the hazards identified, risk assessment was used to identify control measures in order to mitigate, as well as, eliminate hazards in the system by applying some controlling method such as, personal protective equipment, administrative and engineering control which would subsequently be monitored in order to establish a safety system for the plant. Meanwhile, wastes-related risks are also identified and mitigated in purpose study plant. iii A total of forty-one important hazard items were identified at the JOR power station system. These hazards were mainly identified by means of checklists which were sourced from literature and subsequently customized for the current purpose. Risk assessment was conducted by initially classifying the hazards into three levels such as Low, Medium and High. Generally 66% of the hazards identified were at low risk, 32% at medium and 2% at high risk. This indicated that there was sufficient awareness and commitment to safety and health at the Sultan Yusuf Hydro Electric Power generation Plant (JOR power station). There was a resident safety officer in place with a safety committee who together ensure the safety and health of the plant. Meanwhile the JOR Power Station was also certified by MS 1722:2005, OHSAS 18001, MS ISO 14001:2004, MS ISO 9001:2000 and scheduled waste regulation 2005 which give credibility to the current study in creating a working framework which may find widespread application in the future. This study was with a view to creating a model which may be used to identify hazards and assess risks at similar power generation plants of a hydro electric nature, as well as, to enable new hydro electric power generation plants to put a safety system in place.